Performance analysis of data mining tools cumulating with a proposed data mining middleware - Hen, Lai Ee; Lee, Sai Peck (2008)
Data mining has becoming increasingly popular in helping to reveal important knowledge from the organization's databases and has led to the emergence of a variety of data mining tools to help in decision making. Present study described a test bed to investigate five major data mining tools, namely IBM intelligent miner, SPSS Clementine, SAS enterprise miner, oracle data miner and Microsoft business intelligence development studio. Present studies focus on the performance of these tools. Results provide a review of these tools and propose a data mining middleware adopting the strengths of the tools.